Pengukuran Tingkat Capability IT Governance pada PT. Sarana Citranusa Kabil Menggunakan Framework Cobit 2019 - Suroto , Suroto; Friadi, John (Penerbit Goodwood, 2023)
Purpose: This research aims to measure the capability level of IT Governance at PT Sarana Citranusa Kabil (SCN) - Batam, and then provide recommendations related to IT processes that have not reached the target capability level. This research is expected to assist companies in realizing the level of IT Governance capability in accordance with the targets set by the company. Method: The data obtained directly from the respondents were obtained from the results of questionnaires, interviews and observations. The COBIT 2019 framework was developed to measure the level of process capability using the Process Assessment Model (PAM). Result: This research found that the Capability level of 40 IT processes for all domains in IT Governance at PT. SCN is currently at level 3.5 or the specified level. This means that IT Governance based on COBIT 2019 at PT. SCN has been standardized, documented, communicated and implemented. Conclusion: The results found that the level of IT Governance measurement capability of 40 IT processes for all domains in the SCN is currently at level 3.5 or the specified level. This means that IT Governance based on COBIT 2019 at SCN has been standardized, documented, communicated and implemented. Contribution: This research is expected to assist companies in realizing the level of IT governance capability in accordance with the targets set by the company.